1987
DOI: 10.1063/1.339302
|View full text |Cite
|
Sign up to set email alerts
|

Silicon surface cleaning by low dose argon-ion bombardment for low-temperature (750 °C) epitaxial deposition. II. Epitaxial quality

Abstract: Quantum scattering and adiabatic channel treatment of the low-energy and low-temperature capture of a rotating quadrupolar molecule by an ion J. Chem. Phys. 120, 9989 (2004); 10.1063/1.1724822Electrical quality of lowtemperature (T dep=775°C) epitaxial silicon: The effect of deposition rate Electrical quality of lowtemperature (T dep≤800°C) epitaxial silicon: The effect of deposition temperature Silicon surface cleaning by low dose argonion bombardment for lowtemperature (750°C) epitaxial silicon deposition. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The reactor and procedures employed here have been discussed previously (1,2). An optimized low energy, low dose argon ion sputter process is used to remove native oxide immediately prior to deposition.…”
Section: Vlpcvd Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactor and procedures employed here have been discussed previously (1,2). An optimized low energy, low dose argon ion sputter process is used to remove native oxide immediately prior to deposition.…”
Section: Vlpcvd Experimentsmentioning
confidence: 99%
“…Previous PECVD epitaxy research has focused on the role of a plasma in enhancing the removal of native oxide and made independent analysis of deposition enhancement difficult. In this work we examine VLPCVD and PECVD growth processes subsequent to an optimized argon plasma sputter cleaning procedure (1,2). Plasma enhancement for crystalline deposition operates as a parallel addition to an existing heterogeneous thermal deposition process.…”
mentioning
confidence: 99%
“…Previous PECVD epitaxy research has focused on the role of a plasma in enhancing the removal of native oxide and made independent analysis of deposition enhancement difficult. We have already discussed development of an optimized in situ sputter clean which allowed the thermal deposition (VLPCVD) of epitaxial films at 750~176 with low dislocation densities which were suitable for the fabrication of bipolar device structures (10,11,14). In this work we examine VLPCVD and PECVD growth processes subsequent to an optimized argon plasma sputter cleaning procedure.…”
Section: Pecvd For Crystalline Materialsmentioning
confidence: 99%
“…Hydrogen-based cleaning procedures have been explored in the past, e.g. see [36,[40][41][42]. It has been shown that hydrocarbons can be removed using an H 2 plasma [43].…”
Section: Post Etch H 2 /Ar Treatmentmentioning
confidence: 99%